First account of plastic pollution impacting freshwater fishes in the Amazon: Ingestion of plastic debris by piranhas and other serrasalmids with diverse feeding habits. (January 2019) - Andrade, Marcelo C.; Winemiller, Kirk O.; Barbosa, Priscilla S.; Fortunati, Alessia; Chelazzi, David; Cincinelli, Alessandra; Giarrizzo, Tommaso
Abstract: Reported here is the first evidence of plastic ingestion by freshwater fishes in the Amazon. Plastic bags, bottles, fishing gear, and other products are entering Amazonian water bodies and degrade into meso- and micro-plastic particles that may be ingested, either directly or indirectly via food chains, by fishes. Examination of stomach contents from 172 specimens of 16 serrasalmid species from lower Xingu River Basin revealed consumption of plastic particles by fishes in each of three trophic guilds (herbivores, omnivores, carnivores). Overall, about one quarter of specimens and 80% of species analyzed had ingested plastic particles ranging from 1 to 15 mm in length. Fourier transform infrared spectroscopy indicated 12 polymer types, including 27% identified as polyethylene, 13% polyvinyl chloride, 13% polyamide, 13% polypropylene, 7% poly(methyl methacrylate), 7% rayon, 7% polyethylene terephtalate, and 13% a blend of polyamide and polyethylene terephtalate. Dimensions of ingested plastic particles varied among trophic guilds, even though the frequency and mass of ingested particles were not significantly different among fishes with different feeding habits. Highlights: First report on plastic ingestion by Amazon fishes. Plastic debris are ingested by fishes regardless of trophic guild. No difference in number or mass of plastic eaten. No difference in size of microplastics. Difference in size of mesoplastics across guilds.